Assessment of cyclosporin A exposure and identification of variability factors in the early posttransplantation period - Roganović, Maša; Cvetković, Mirjana; Gojković , Ivana; Spasojević, Brankica; Kostić, Mirjana; Miljković, Branislava; Vučićević, Katarina (Archives of Pharmacy, 2022)
Cyclosporin A (CyA) is an immunosuppressant used as part of a post-transplant therapeutic protocol to prevent graft rejection. Due to the large pharmacokinetic variability that characterizes it, it is necessary to conduct therapeutic drug monitoring (TDM). The aim of the conducted research is to assess the exposure of CyA in the period of up to 3 months after transplantation (early post-transplantation period) with the identification of factors that influence the values ​​of the pharmacokinetic parameters of CyA. From pediatric patients with kidney transplants, at the University Children´s Hospital Tiršova, data about dosage regimens, cotherapy, and measured CyA concentrations (C0 - immediately before the next dose and C2 - 2 hours after the morning dose) were collected retrospectively. Data were analysed in NONMEM® (version 7.4). Twenty six patients (up to 12 years old) were included in the analysis. The pharmacokinetic model that best described the data is a one-compartment model with first-order absorption. Haematocrit, serum creatinine and body mass were identified as the main factors of variability. In further analysis, it is necessary to include data about genetic polymorphism, which is expected to have the greatest impact on drug exposure and change the power ratio of factors that influence CyA parameter values ​​and concentrations.The obtained results are expected considering the characteristics of CyA. In addition to identification, quantification of the influence of the mentioned factors is crucial for establishing an optimal dosing regimen in the early post-transplantation period in children, when the risk of graft rejection is the highest.